Informality and Working Conditions in China's Sanitation Sector - Zhang, Hao; Friedman, Eli (The China quarterly (London), 2019)
Drawing on ethnographic data from the sanitation industry in Wenzhou and Guangzhou, we investigate different patterns of work organization in each city. We find that supplementary informal work can serve to subsidize low family income and therefore stabilize formal but exploitative work. In Wenzhou, the family team model creates time and space for one spouse to engage in informal work while still receiving a wage from the employer. This additional informal work significantly increases net family income, which neutralizes worker demands for better wages and working conditions in the formal sector. In contrast, Guangzhou workers are subject to relatively rigid spatio-temporal controls, impeding them from participating in informal work to supplement their formal wages. Despite receiving higher wages and more benefits, these workers are highly wage dependent and express much greater discontent than their equivalents in Wenzhou. Theoretically, we contribute to the literature on informality through a discussion of “ancillary informal work,” highlighting how access to certain kinds of informal work both subsidizes and is facilitated by formal sector employment. 通过对温州和广州的民族志调查，我们研究了两个城市的环卫行业不同的工作组织模式。我们发现: 补充性的非正规工作可以为低收入家庭提供一定的收入补贴，并因此能够稳定那些虽是正规但却非常剥削性的工作。在温州，家庭团队的工作模式为两个配偶之一提供了便利的时间和空间，使其在从雇主处得到一份工资的同时还得以从事一些非正规工作。这些额外的非正规工作显著地增加了家庭总收入，也避免了工人在正规部门提出更高工资和更好的工作条件的要求。与此相反，广州环卫工人被置于了相对僵化的时空控制之下，从而阻碍了他们从事非正规工作来补充其正式工资的机会。尽管他们的正式工资和福利待遇都比温州环卫工更高，广州环卫工却非常地依赖这份工资，并且表现出了更强烈的不满。理论上，我们为非正规就业的研究贡献并讨论了“附属性非正规工作”的概念。这一概念揭示了某些类型的非正规工作是如何一方面补贴了正规部门的就业，而另一方面又为后者所促进。